Control of phycocyanin production from Spirulina platensis in fed-batch reactor using mid course correction policy - Nor Fatihah, Ab Ghani (2012)
Phycocyanin is a product of cultivation of Spirulina platensis,a blue-green microalga. Phycocyanin is widely used in medical treatment as a cancer inhibitor and as a natural dye for cosmetics and foods.Spirulina platensis has been cultivated recently in fed batch reactor to optimize the cell growth and product formation.Large scale production of Spirulina platensis gives more advantage especially in production cost but it is hard to control the final product to the desired value due to the disturbance occurred during the cultivation process. Therefore,Mid-Course Correction (MCC)policy is introduced to the process.Throughout the MCC,a model predictor is constructed to predict the final product concentration based on the previous experimental data.A control model is build for phycocyanin production based on the light intensity adjustment.The adjustment is made on day 5 of the cultivation process and simulation is done to recheck whether the final phycocyanin production is fall in the desired range.